Examen especial a la cuenta corriente del banco de Loja de supermercado Maxce periodo enero a junio del 2014 - Rey Ajila, María Cristina (2016)
For the development of special consideration to the current account of the bank of Loja Supermarket Maxce in the period January to June 2014, "lies the development and fulfillment of requirements according to the Academic Regulations for obtaining engineering degree in Accounting and audit Certified Public Accountant Auditor, also helps the company to keep better management, control of bank transactions to get reconciled balances, allowing to know the accuracy of the balances presented an internal control model was delivered to have a clear economic position company. In developing this work, it will comply with the main objective of the special examination to the bank account of Supermarket Maxce by conducting planning, starting with the assessment of internal control questionnaire method, the same to help us with information on compliance provisions of the company, applying techniques and audit procedures to obtain evidence which contain comments, conclusions for the sustenance of the final report, also help verification of information, promoting reasonableness of the transactions and balances of the current account, low physical verification of working papers that helped meet goals set ensuring the processes established in accounting principles and standards. Upon completion of the special examination to determine efficiency and effectiveness of resource management, financial and accounting operations are concluded, issuing the final report of the Review, announcing the Managing Owner recommendations and conclusions drawn.